The Detection of Seismicity on Icy Ocean Worlds by Single‐Station and Small‐Aperture Seismometer Arrays. Issue 3 (4th March 2022) - Marusiak, A. G.; Schmerr, N. C.; Pettit, E. C.; Avenson, B.; Bailey, S. H.; Bray, V. J.; Dahl, P.; DellaGiustina, D. N.; Wagner, N.; Weber, R. C.
Abstract: Future missions carrying seismometer payloads to icy ocean worlds will measure global and local seismicity to determine where the ice shell is seismically active. We use two locations, a seismically active site on Gulkana Glacier, Alaska, and a more seismically quiet site on the northwestern Greenland Ice Sheet as geophysical analogs. We compare the performance of a single‐station seismometer against a small‐aperture seismic array to detect both high (>1 Hz) and low (<0.1 Hz) frequency events at each site. We created catalogs of high frequency (HF) and low frequency (LF) seismicity at each location using an automated short‐term average/long‐term average technique. We find that with a 1‐m small‐aperture seismic array, our detection rate increased (9% for Alaska and 46% for Greenland) over the single‐station approach. At Gulkana, we recorded an order of magnitude greater HF events than the Greenland site. We ascribe the HF events sources to a combination of icequakes, rockfalls, and ice‐water interactions, while very HF events are determined to result from bamboo poles that were used to secure gear. We further find that local environmental noise reduces the ability to detect LF global tectonic events. Based upon this study, we recommend that (a) future missions consider the value of the expanded capability of a small array compared to a single station, (b) design detection algorithms that can accommodate variable environmental noise, and (c) assess the potential landings sites for sources of local environmental noise that may limit detection of global events. Plain Language Summary: To better prepare for future planetary missions, we deployed seismometers on glaciers and ice sheets, environments on Earth that mimic those of icy ocean worlds. We compare the ability of a single seismometer versus several seismometers in detecting different types of earth and ice quakes and to compare widely different sites with respect to local environmental noise such as ice cracking, melt water from the glacier, and rock falls off nearby mountains. We find that multiple instruments separated by only 1 m can better detect large tectonic events than only one instrument. Further, if the site has low level of environment noise, we detect more large tectonic events. Small local events, however, can help characterize the local environment. We also detected events from equipment left at our field site. Future missions would benefit from sending multiple seismometers instead of just one. If a mission wants to study the whole planet or moon, then the landing site should be situated away from any active surface features and a single seismometer should be sufficient. If the goal is to study a specific active feature or region, then the landing site needs to be close to that feature. Key Points: Small‐aperture arrays (2 m) have higher detection rates (9%–46%) of regional and teleseismic events compared to a single‐station Low noise sites allow more detection of global tectonic events, but offer less characterization of local environment A single‐station seismometer in an icy ocean world analog setting can effectively detect and locate local seismicity